Percepciones de los estudiantes, docentes y directivas de la IED Pio X de Chipaque Cundinamarca acerca de las implementación de la jornada única, una posibilidad de mejoramiento institucional (2017)
This research studied the perceptions from students, teachers and managers towards the implementation of the full school day in the Pio X I.E.D in Chipaque, Cundinamarca, to recognize the possible institutional improvement factors and to support other institutions that would implement this policy, by means of a qualitative approach, observed within the hermeneutics interpretative paradigm and with a phenomenological methodology. As a conclusion from this research, the need to build a preliminar proyect in the institutions that will implement the full school day, with the involvement of all the educational community is revealed. Such project should take into account the institutional context and, also, all the aspects of the national legislation of the full school day.